Multinational corporations' effective tax rates: Evidence from orbis - Petr Janský; Javier Garcia-Bernardo; Thomas Torslov (Charles University in Prague, Institute of Economic Studies (IES), 2020)
Effective tax rates (ETRs) estimated from the balance sheet data of multinational corporations (MNCs) are useful for comparing MNCs' corporate income taxation across countries. In this paper we propose a new methodological approach to estimate ETRs as reliably and as for as many countries as possible using Orbis' unconsolidated data for the 2011-2015 period. We focus on countries with at least 50 available companies, which results in a sample of 50, mostly European, countries. We estimate the ETR of a country as the ratio of corporate income tax to gross income for all affiliates of MNCs in that country, weighted by gross income. We propose four ETR estimations, including lower and upper bounds, which differ by gross income calculation. We find that ETRs substantially differ from statutory rates for some countries. For example, we show that despite similar statutory rates of 28% and 29%, MNCs in Luxembourg paid as little as 1-8% of gross income in taxes while those in Norway paid as much as 45-66%. Despite being the best available, existing data is still imperfect, and we therefore call for better data in the form of MNCs' unconsolidated, public country-by-country reporting data.
Keywords: C81; F21; F23; H25; H26; 330; Effective tax rate; multinational corporation; foreign direct investment; profit shifting; tax haven; tax competition